PRODUKSI TIGA VARIETAS RUMPUT PADA LAHAN TERLANTAR DENGAN DOSIS PUPUK KANDANG YANG BERBEDA - Habibul Akram; Muhammad Husaini Assauwab; Hadirin Hadirin; Halisah Suriani (KOLONI, 2022)
As the number of ruminants continues to increase from 2017 to 2021, especially ruminants in Southeast Aceh District, the need for forage for fodder must increase and the availability of feed throughout the year but the availability of forage is experiencing obstacles. The experiment was arranged according to a randomized block design with three replications. The study aims to obtain forage for the three varieties suitable for cultivation on abandoned land in Pulo Gadung Village, Darul Hasanah District, Aceh Teggara Regency. Study plot The first factor was the dose of manure (P) consisting of: P0 = 0 tons -1, P1 = 5 tons -1, P2 = 10 tons -1, and P3 = 15 tons -1. The second factor is the type of grass (R), which consists of: R1 = Elephant Grass (Pennisetum purpureum L), R2 = Mini Elephant Grass (Pennisetum purpureum cv mott) and R3 = Setaria Grass (Sphacelata). Gajarh grass of Pennisetum purpureum L (R1) variety, which had more dominant number of shoots, plant height, and fresh weight compared to other treatments. Manure can increase the number of shoots, plant height and fresh weight of elephant grass. The best interaction between manure doses and elephant grass varieties was shown in the P3R1 treatment. Keywords: Organic, Feed, Fertilizer, Grass, Livestock